Citrullination – small change with a great consequence - Gogól, Mariusz (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2013)
Citrullination is one of the possible post-translational modifications of proteins. It is based on a conversion of L-arginine residue (L-Arg) to L-citrulline residue (L-Cit). The reaction is catalyzed by peptidylarginine deiminases (PAD). The change of L-Arg imino moiety results in a loss of a positive charge. This slight modification can contribute to significant changes in physicochemical properties of proteins, which may also cause a change of their functions. Citrullination is the modification observed in physiological processes such as epidermal keratinization, regulation of gene expression and the reorganization of myelin sheaths. The changes in the efficacy of citrullination may contribute to the pathogenesis of many different diseases including: psoriasis, multiple sclerosis, rheumatoid arthritis and cancer.